Karakterisasi Morfologi Tanaman Kelapa Sawit (Elaeis Guineensis Jacq. ) Di Kebun Binaan Ppks Kabupaten Dharmasraya - Ikal Idris; Reni Mayerni; Warnita (Jurnal Riset Perkebunan, 2020)
Oil palm is an important industrial crop as a producer of oil and fuel Palm oil produces various derivative products that are rich in benefits in the food, pharmaceutical, and cosmetic industries.. Minyak kelapa sawit This research was carried out in the Oil Palm Research Center (PPKS) development garden in Sungai Dareh, Pulau Punjung District, Dharmasraya . The research was conducted for 3 months on December 2018 until February 2019. The objective of this study was to know the morphological characters of oil palm (Elaeis guineensis Jacq.) D x P Marihat variety (results of tissue culture) and D x P Sungai Pancur variety (results of conventional crossing) in PPKS development garden , Dharmasraya. The research method was a descriptive method, by this method the researcher can see and explain the morphological characteristics of oil palm plants. Sampling was by purposive sampling. The results showed that there are different variations on 9 observed variables whereas one similarity was obtained on variable phyllotaxis between varieties D x P Sungai Pancur and D x P Marihat in the PPKS development garden in Sungai Dareh, Pulau Punjung District, Dharmasraya.